Development and Validation of an Analytical Procedure for the Quantitative Determination of Total Flavonoids in Red-Stem Buckwheat Herb (Fagopyrum rubricaulis) by Spectrophotometry - A. V. Mitishev; E. E. Kurdyukov; M. G. Makartseva; Y. M. Nemova; D. G. Elistratov; A. S. Paksyaev (Регуляторные исследования и экспертиза лекарственных средств, 2023)
INTRODUCTION. Red-stem buckwheat (Fagopyrum rubricaulis, Polygonaceae family) is characterised by a high content of flavonoids, primarily rutin. The aerial parts of the plant also contain quercetin, isoquercetin, orientin, vitexin, isoorientin, and other compounds. F. rubricaulis has antioxidant, cardioprotective, hypoglycaemic, and antibacterial pharmacological effects, which are attributed to the complex of flavonoids in the plant. Therefore, F. rubricaulis herb can be standardised using the content of total flavonoids. However, Russian publications lack information on the standardisation of F. rubricaulis herbal drugs. This motivates the development of an analytical procedure for the quantitative determination of flavonoids in F. rubricaulis.AIM. This study aimed to develop and validate an analytical procedure for the quantitative determination of flavonoids in F. rubricaulis herb by spectrophotometry.MATERIALS AND METHODS. The study involved extracting F. rubricaulis herb samples using several extraction solvents (purified water and 40%, 70%, and 95% ethanol). The presence of flavonoids in the herbal drug was confirmed by thin-layer chromatography (TLC). The content of flavonoids in F. rubricaulis herb was determined using a spectrophotometric procedure based on measuring the absorbance of the test solution in the presence of aluminium chloride. The analytical procedure was validated according to the State Pharmacopoeia of the Russian Federation (edition XV).RESULTS. The TLC identification confirmed that the F. rubricaulis herb hydroalcoholic extracts contained flavonoids. The analytical procedure for the quantitative determination of flavonoids by differential spectrophotometry involved preliminary single-step hydroalcoholic extraction (herbal drug sample size: 1 g, accurately weighed; fragment size: ≤2 mm; extraction solvent: 40% ethanol; sample-to-solvent ratio: 1:25; extraction time: 30 minutes). The absorption maxima of the complexes of flavonoids with aluminium chloride were at 410 nm, which corresponded to the absorption maximum of the rutin standard solution. The content of total flavonoids was expressed as rutin. The analytical procedure was validated for specificity, linearity, repeatability, and intermediate precision. The developed analytical procedure was used to test 4 samples of F. rubricaulis herb manufactured by Parafarm LLC. The content of total flavonoids (expressed as rutin) ranged from 9.15±0.20% to 9.55±0.11%.CONCLUSIONS. This study developed and validated a spectrophotometric analytical procedure for the quantitative determination of the content of total flavonoids (expressed as rutin), which can be used to standardise F. rubricaulis herbal drugs.